Exploratory Data Analysis and Offence Prediction - et al., Vivek Gaurav Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big data is a part of data science that pinpoint different ways to diagnosis, systematically withdraw facts from informational collections that are excessively enormous or complex to be managed by customary information handling application software. Big Data Analytics(BDA) is a specific tactic for breaking down and recognizing assorted examples, kindred, and patterns inside a massive volume in order. Big data analytics (BDA) is a meticulous approach to data analysing and recognising unique layers, connections, and trends ina gigantic volume of data. We apply BDA to illegitimate information collected in this paper, where preliminary data analysis was conducted for visual analysis and trend prediction. Following statistical analysis and visualisation, some incredibly interesting facts and patterns emerge from illegal data in INDIAN states i.e. (Uttar Pradesh, New Delhi, Goa). The prognostic results demonstrate that Kerasstateful LSTM execute enhanced than neural network models. These capable outcomes will allow police departments and law enforcement agencies to better understand crime problems and gain insights that will allow them to schedule activities, predict the likelihood of incidents, efficiently allocate resources, and optimise decision making.